Breaking the Vicious Cycle: Smoking, Low Education, and Poverty in Tangerang Regency - Sena Atmaja; Helmas Septiyo Hadi; Abu Naim; Resy Perwithasari (IECON: International Economics and Business Conference, 2025)
This study investigates the interconnection between smoking behavior, educational attainment, and poverty in Tangerang Regency, Indonesia. Utilizing secondary data from the Central Statistics Agency (BPS) and the Ministry of Health (2023), the analysis reveals that smoking prevalence is highest among individuals with lower educational levels, particularly within economically productive age groups. Despite living close to the poverty line, many households allocate more of their income to tobacco than to essential food items, highlighting a pattern of non-productive spending. The findings indicate a vicious cycle where limited education leads to harmful health behaviors, which in turn reinforce economic hardship. To address this, the study proposes integrated public policies aimed at improving educational access and implementing stricter tobacco control measures. These efforts are crucial to breaking the poverty trap and promoting long-term social welfare.